The Relationship between Learning Style Preferences and Reading Strategy Use in English as a Foreign Language - Lesiak-Bielawska, Elżbieta Danuta (Glottodidactica, 2008)
The study explored the relationship between learning style preferences and the use of reading strategies triggered during the performance of a reading comprehension assignment in English as a foreign language (EFL). The research conducted drew on the hypothesis that the type of language task activates a battery of strategies that reflect the subject's learning style preferences and the task requirements.